Computer Simulation of Turbulent Flow Phenomena in Nuclear Fuel Pin Subassemblies - Hisashi Ninokata; Elia Merzari (Institut Teknologi Bandung, 2008)
This paper focuses on the turbulence phenomena that have been identified by computational fluid dynamics (CFD), and that are peculiar to the flows in tight lattice nuclear fuel subassemblies, eccentric annuli and two-rectangular channels interconnected by a narrow gap. The CFD methods employed are the Direct Numerical Simulation of turbulence (DNS) and Large Eddy Simulation (LES) techniques. Highlighted phenomena include turbulence-driven secondary flows inside a subchannel, local turbulent-laminar transition in the narrow gap region between two adjacent fuel pins, and global pulsation of the flow across the length of a fuel subassembly. Special attention will be paid on linkage to the physics, limitation of the computational capability of the CFD methods, and the usefulness of the technology in reference to the foreseeable future.